Boo: Peek-a-Boo Baby - Waring; Zoe (Great Britain Pat-a-Cake, 2020)
Young children learn best through interactive play and Peek-a-Boo Baby: Boo! helps parents and carers with this as they share a story with their child sitting on their lap. Simple questions and funny pictures of silly Halloween spooks hiding under the flaps will have babies squealing with delight as they play, point, laugh, say hello and play peek-a-boo!